Lead and Cadmium Pollution: Implications for Health in Artisanal and Small Scale Gold Mining in Senegal and Kenya - Leonard , Agan; Khazenzi, Judith; Kandioura , Noba; Osano, Odipo (African Journal of Education,Science and Technology (AJEST), 2024)
Artisanal and Small-Scale Gold Mining (ASGM) is a prevalent activity, characterized by low-tech equipment and inadequate Occupational Health and Safety Standards (OHS). The ASGM is a significant source of Potentially Toxic Elements (PTEs), which can result in potential health risks to humans and the ecosystem. The interconnectedness between human and environmental health have gained global attention from scientific communities, public health and planetary health regarding human-environmental continuum’s safety. This study aimed at assessing human and environmental health risks associated with mine pollution in Kedougou region of South Eastern Senegal and Kakamega region in Western Kenya. Purposive sampling was used to collect waste ores, agricultural soil, residential soils and surface water samples were taken from Kedougou region while secondary data on similar matrices were used from Kakamega region. Descriptive statistics, figures and tables were used to present the result. Health risks assessment were achieved using Enrichment Factors (EF), Index of Geo-accumulation (Igeo), Pollution Index (HPI), and Ecological Risk Assessment Indices (ERI); to ascertain the source and the burden of health risk as a result of contamination in the two regions. Distinct geological and mineralogical compositions contributed significantly to the difference in concentrations of these Pb and Cd across Eastern and Western Africa regions. Further, geographic variation in background concentrations contributed significantly to the natural Pb and Cd levels in environmental media between the different locales. This research concluded that ASGM is one of the contributors to human and ecosystem health risks associated with Pb and Cd pollution. There is urgent need for comprehensive Occupational Health and Safety Standards; implementation and training of miners to safeguard human health while maintaining the livelihood in ASGM operations as well as proper control of mine waste disposal and conservation measures around the ASGM areas.